Cormac McCarthy´s The Stonemason and the Ethic of Craftsmanship - Federico Bellini (European Journal of American Studies)
The Stonemason (1995), Cormac McCarthy’s first published play, is a sustained meditation on the values of the ethic of craft as opposed to mere work, as well as on the difficult application of such values to reality. On the one hand, craft is represented as the quintessential value; on the other, it is measured against the real world in which values have to be constantly renegotiated in order to be useful. In this essay, I analyze how the tension between the ideal of the “craftsman hero,” represented by Papaw, and Ben’s attempt to live up to it traverses The Stonemason through three distinct if intertwined levels. First is the individual level, at which craft is intended as Ben’s personal experience of learning from Papaw how to lay stone upon stone as he struggles to hold his family together. Second is the social level: stonemasonry is one element of the economic system which is the battlefield for the struggle between the effort of the oppressed to improve their position and the ever-renewing ways in which the oppressors defend and exercise their power. Finally, there is the symbolic-mythical level: here stonemasonry is seen as the archetypical craft embodying a view of the world as the product of either a benevolent or an evil God. It is in the tension between the ideal and the reality of craftsmanship as it crosses these three dimensions that one can appreciate the full scope and complexity of McCarthy’s ethic of craft.